Sheep tail fat inhibits the proliferation of non-small-cell lung cancer cells in vitro and in vivo - Xu, Changzhi; Zhang, Lanlan; He, Huimin; Liu, Xiaoyi; Pei, Xinxin; Ma, Tengfei; Ma, Bingbing; Lin, Wenchu; Zhang, Buchang (Frontiers in Pharmacology, 2022)
Increasing evidence suggests that numerous edible oils may function as adjuvant dietary therapies to treat cancer. We previously reported that the odd-chain saturated fatty acid (OCSFA), heptadecanoic acid (C17:0), profoundly inhibits non-small-cell lung cancer (NSCLC) cell proliferation. However, the antitumor potential of edible lipids rich in C17:0 remains unclear. Here, we determined that sheep tail fat (STF) is a dietary lipid rich in C17:0 and exhibited the greatest inhibitory effect against three NSCLC cell lines (A549, PC-9, and PC-9/GR) among common dietary lipids. Cell migration experiments demonstrated that STF could significantly inhibit the wound healing capacity of three NSCLC cell lines by promoting the generation of reactive oxygen species (ROS) and subsequent cell death. Mechanistic studies showed that STF suppressed NSCLC cell growth by downregulating the Akt/S6K signaling pathway. Furthermore, administration of STF reduced tumor growth, weight, and expression of the proliferative marker Ki-67 in nude mice bearing A549 xenografts. Collectively, our data show that STF has antitumor activity against NSCLC, implying that dietary intake of C17:0-rich STF may be a potential adjuvant therapy for NSCLC.